PENDIDIKAN DI ERA DIGITAL - Verdinandus Lelu Ngongo; Taufiq Hidayat; Wiyanto Wiyanto (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Nowadays the increasing on information of technology can not be depated wit education. The education must be follow the information technology and communication. The education in digital era can be able to integrated with information technology and communication into the whole lessons. The increasing education in digital era thestudent can be understand many skills easily. The impact of inovation is learning technology method of study using experiment of technology. The change of the duty of the education needs inovation and creativities in learning process. The new technology meanly multimedia is the important thing and learning activities. With multimedia can be variation in the situation of lesson and the student enjoy the lesson. So that the teacher as a teacher must be integrated the information technology and communication into learning well and every day can be increasingly the education quality in Indonesia.